Biomonitoring of nickel air pollution near the city of Kavadarci, Republic of Macedonia - Bačeva, Katerina; Stafilov, Trajče; Šajn, Robert (Macedonian Journal of Ecology and Environment, 2009)
Air pollution with nickel was investigated in the vicinity of the ferronickel smelter plant near the city of Kavadarci, Republic of Macedonia. In this work the moss biomonitoring technique and atomic emission spectrometry with inductively coupled plasma was applied. The purpose of the study was to establish range of air pollution with nickel which could be expected due to the pollution from the ferronickel plant. For this purpose, 35 moss samples were collected together with 19 soil samples taken from the same localities as a topsoil (0-5 cm) and subsoil (20-30 cm). The analyses of moss and soil samples were performed using atomic emission spectrometry with inductively coupled plasma. The obtained results show that there is evidently higher content of nickel in moss samples collected in the vicinity of the ferronickel smelter plant. The median value of Ni in moss samples from the whole region (31.0 mg kg-1) is much higher that the median for Macedonia (2.4 mg kg-1). This fact confirms the influence of the air pollution with dust from the ferronickel plant in the larger region of city of Kavadarci.